UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU SDK COAL - Stefania So’o; Ambros Leonangung Edu; Florianus Dus Arifian (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2022)
Professional competence of teachers at SDK Coal is still low. They rarely pay attention to the efforts to improve their competence. Therefore, this study aims to describe the the competency of SDK Coal teachers and how to improve itut. The type of research used is descriptive research with a qualitative approach. The subjects were SDK Coal teachers and school principal. Data collection techniques using interviews, observation, and documentation. The results show that the professional competence of SDK Coal teachers is not up to the expected standard, as can be seen from: a) competence in mastering the subject matter broadly and deeply. Teachers are fixated on source books during the learning process, they are difficult to apply concepts, and use existing sources without trying to find other sources; b) Competence in mastering the subject curriculum. Teachers do not prepare lesson plans (RPP) and tend to use conventional methods and strategies. c) Less able to develop the material in a sustainable manner with reflective actions. The teachers have not packaged learning materials properly, have not actively participated in seminar activities, and training in writing and publishing scientific papers. Based on the description above, it can be concluded that the teachers at SDK Coal have not fully made efforts to improve professional competence